Strategi Penguatan Pendidikan Karakter Dalam Pembelajaran Berbasis Moda Daring - Baso Intang Sappaile; Dewi Prabawati; Muhammad Yasin; Andi Tenri Abeng; Nuridayanti Nuridayanti; Siyono Siyono (Departement of Mathematics Education, 2023)
Character education is very important for individuals to be instilled early on. It is the accuracy of character education that will determine the results. In online mode-based learning, distance learning must have various learning strategies and appropriate reinforcement that can maintain student character in following the learning process. This study aims to determine the strategies used in strengthening character education in online mode-based learning. This research uses a descriptive qualitative approach. Data collection techniques through observation and literature study. The results of this study indicate that the strategy of strengthening character education in online mode-based learning is a series of activities that need to be carried out in improving the quality or quality of education. In improving the quality of education, it must be done with a strategy of choosing a good teaching method that is relevant to the current situation. The strategy designed is made with something active, innovative, creative, and fun and motivates students to stay active in online mode-based learning. Strategies like this can also help students from their psychological conditions because students feel bored with online learning at home with repeated and continuous time.